Re-Thinking & Improvise Uses Of Negative Space Under The Flyover: Parking Spaces - Husnil, Muhammad Asraf (2019)
In this decade, the issue of using public spaces in cities for social interactions is very critical. One of the public spaces that is usually used by people is the area under flyovers. This study aims to rethink and focus on making use of space under flyovers by turning them into parking spaces. The study will include a few locations in Malaysia such as under Jalan Yew Kuala Lumpur, under Gelugor Highway & under Bayan Lepas Expressway Penang. The objective of this study is to solve the problem which is to convert improper parking at the negative space under the flyover by proposing solution of utilising the area under flyovers (flyunder) in a legal manner to authorities. Besides that, this research also aim to create a proposal guideline and recommendation for using the space under the flyovers as carparks. After planning the framework for the study of spaces under flyovers, a comprehensive study of the rules and regulations, and functional characteristics of the spaces below the flyover was made.